2013
DOI: 10.1007/s11999-013-2818-9
|View full text |Cite
|
Sign up to set email alerts
|

Slipped Capital Femoral Epiphysis: Relevant Pathophysiological Findings With Open Surgery

Abstract: Background Traditionally arthrotomy has rarely been performed during surgery for slipped capital femoral epiphysis (SCFE). As a result, most pathophysiological information about the articular surfaces was derived clinically and radiographically. Novel insights regarding deformity-induced damage and epiphyseal perfusion became available with surgical hip dislocation. Questions/purposes We (1) determined the influence of chronicity of prodromal symptoms and severity of SCFE deformity on severity of cartilage dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 37 publications
(73 reference statements)
5
74
1
5
Order By: Relevance
“…It is unclear, however, whether revascularization was related to the integrity of the retinacular vessels or if it may have happened through a transphyseal mechanism. Contrary to previous studies [9,18,30], we found three patients with an ICP waveform before dissection and after fixation who later developed osteonecrosis. These represent examples of a false-negative test result.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…It is unclear, however, whether revascularization was related to the integrity of the retinacular vessels or if it may have happened through a transphyseal mechanism. Contrary to previous studies [9,18,30], we found three patients with an ICP waveform before dissection and after fixation who later developed osteonecrosis. These represent examples of a false-negative test result.…”
Section: Discussioncontrasting
confidence: 99%
“…All three patients developed osteonecrosis. However, in accordance with Ziebarth et al [30], we observed two patients with an intact retinacular flap in whom there was no intraoperative ICP waveform and who did not development of osteonecrosis. These represent examples of a false-positive test result.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations